18=3(g-12)+3

Simple and best practice solution for 18=3(g-12)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18=3(g-12)+3 equation:



18=3(g-12)+3
We move all terms to the left:
18-(3(g-12)+3)=0
We calculate terms in parentheses: -(3(g-12)+3), so:
3(g-12)+3
We multiply parentheses
3g-36+3
We add all the numbers together, and all the variables
3g-33
Back to the equation:
-(3g-33)
We get rid of parentheses
-3g+33+18=0
We add all the numbers together, and all the variables
-3g+51=0
We move all terms containing g to the left, all other terms to the right
-3g=-51
g=-51/-3
g=+17

See similar equations:

| 4(z-2)=-20 | | 5x+28=68 | | 5m-2=16-4m | | 8x-28=15x-6 | | x/12=22 | | (5a+8)(4a-10)=18 | | d+8➗-2=1 | | 1/y=-1 | | 2(y+1)+2=6 | | -2(g-19)=6 | | (3x)+(2x+20)=90 | | 3(g-6)=9 | | 3(g-6=9 | | 2(7x+2)=13x+3 | | 6(5x-3)=3(3x+29) | | (x+9)+(2x-44)=180 | | 8/9x-9=7 | | (x+9)+(2x-44)=90 | | (x+9)+(x-44)=90 | | 8/9x-7=17 | | 9x-8=-70I | | 274=152-y | | 121000(1+r)^-2=100000 | | 8(x+4)=24+18x | | 2/3(12-6)=8(x+2) | | 16x2-151x+88=0 | | 230+2x-(23x-41/(34*0.34x))=39.2 | | 1x/3+8=-1x/2-2 | | 2x/6+10=-3x/6 | | (3x+34)=(12x+33) | | n^2+5n-88=0 | | 2x–8x=12–8x |

Equations solver categories